Alan's coming on to Shakespeare. Issue 6 (18th September 2016) - de Grazia, Margreta
ABSTRACT: There is no separating Alan Sinfield's life from his work; even the rooms of his house reflected their integration. And nowhere did he find so many of his causes and interests than in the cultural bastion Shakespeare. See his reading of the infamous sonnet 20, as shocking as it is irrefutable.